Genetically predicted the causal association between serum mineral elements with immune thrombocytopenia and Henoch-Schonlein purpura: a bidirectional two-sample Mendelian randomization analysis - Yan Chen; Xiuli Hong; Yamei Chen; Zhiqiang Xu; Quanyi Lu (Thrombosis Journal)
Abstract Background Worldwide, the diagnosis and treatment of immune thrombocytopenia (ITP) and Henoch-Schönlein purpura (HSP) remain a major and ongoing challenge in hematology. Emerging clinical evidences suggest serum mineral elements are associated with ITP or HSP, but the causal relationship between them is still unclear. Aims Conducting a two-sample, bidirectional Mendelian randomization (MR) study to evaluate the causal association between serum mineral elements including zinc, copper, magnesium, iron and calcium with ITP and HSP. Methods In this two-sample, bidirectional MR study, summary statistics data of genome-wide association studies (GWAS) on exposures including zinc, copper, iron, magnesium and calcium were extracted from the MRC-Integrative Epidemiology Unit (MRC-IEU). The GWAS data on study outcomes, including ITP and HSP, were obtained from the FinnGen consortium. MR-Egger intercept and MR-PRESSO global test were utilized to assess the heterogeneity and horizontal pleiotropic of instrumental variables (IVs) between the exposures and outcomes, respectively. Inverse variance weighted (IVW) test was used as the primary analysis method to evaluate the causal between serum mineral elements with the risk of ITP and HSP, and weighted-median, weighted model, MR steiger, MR-PRESSO and radial MR were used as auxiliary analysis methods, moreover, the odds ratio (OR) and 95% confidence interval (CI) were calculated. Reverse MR analysis was also conducted. Leave-one-out test was further to conduct whether the association between serum mineral elements and the risk of ITP and HSP remain robust. Results No significant horizontal pleiotropy and heterogeneity between individuals IVs was found after MR-Egger and MR-PRESSO global test. Genetically predicted that high copper (OR = 0.768, 95%CI: 0.628–0.937) and magnesium (OR = 0.314, 95%CI: 0.112–0.884) concentrations may reduce the risk of ITP and HSP, respectively. High calcium concentration may increase the risk of HSP (OR = 1.823, 95%CI: 1.226–2.712). There was no significant evidence to support a causal association between iron, zinc, magnesium, and calcium with the risk of ITP, or between iron, copper, and zinc and the risk of HSP (all P > 0.005). Moreover, no reverse causal associations between five serum mineral elements with the risk of ITP and HSP were found (all P > 0.05), suggesting the causal associations between serum mineral elements with ITP and HSP were not bidirectional. In addition, consistent results were obtained by multiple sensitivity analyses, indicating the associations of serum mineral elements with the risk of ITP and HSP relatively robust. Conclusion In this MR study, we discovered genetically predicted that elevated serum levels of copper and magnesium decreased the risk of ITP and HSP, respectively, and elevated levels of serum calcium increased the risk of HSP. However, no reverse causal association was found between serum mineral elements with the risk of ITP and HSP.